The hyperfine structure of NO(A(2)Sigma(+)) - Brouard, M; Chadwick, H; Chang, Y; Howard, B; Marinakis, S; Screen, N; Seamons, SA; La Via, A (2012)
Hyperfine quantum beat spectroscopy has been combined with an effective Hamiltonian approach to determine the hyperfine structure of NO(A, v). NO(A, v = 0, N = 1-7, 9 J = 1.5-8.5, F = 0.5-8.5) was produced by pulsed dye laser excitation on the 0-0 band of the NO A2Σ+ ← X2Π transition at wavelengths around 226 nm. The observed line frequencies, along with those reported in previous measurements of NO(A, v = 0,3) have been fitted using a non-linear least-squares program with numerical diagonalization of the Hamiltonian matrix. This enabled us to determine the best obtainable sets of hyperfine parameters for the molecule. The vibrational dependence of the hyperfine parameters is discussed in the light of previous experimental and theoretical work on related systems. © 2012 Elsevier Inc. All rights reserved.